P2.192 Vaginal Epithelial Thickness and Serum Hormone Levels by Body Mass Index at the Luteal and Follicular Phases of the Menstrual Cycle. (13th July 2013) - Chang, M; Jones, H E; Dzuba, I G; Ballagh, S; Irwin, T; Marx, P A; Pau, K Y F; Veazey, R; Winikoff, B
Abstract : Background: Obesity is increasing in the United States and is associated with reproductive disorders. Little is known regarding the precise mechanisms by which obesity impacts reproductive health, but many studies have shown alterations to endocrine function in obese women. Further, the endocrine system alters immune system function and regulates vaginal epithelial thickness. Thus, obesity could alter susceptibility to sexually transmitted infections via two distinct biological pathways. Methods: We analysed pre-product use data from a 101 women (aged 18 to 40) with normal menstrual cycles in a Phase I trial to assess the association between body mass index (BMI ≥ 30 compared to BMI < 30), serum hormone levels and vaginal epithelial thickness at two points in the menstrual cycle, the luteal and follicular phase, based on self-reported last menstrual period (LMP). We collected vaginal biopsies at each visit for analysis of epithelial thickness and count of basal, transitional and superficial cell layers, and blood samples for circulating hormone levels. We used median rank sum tests and linear regression models to compare outcomes by BMI status, adjusting for a priori hypothesised confounders. Results: While there was no difference in total median vaginal epithelial thickness between obese and non-obese women, obese women had fewer layers of superficial vaginal epithelium (median of 15.4 vs. 13.3 layers, p = 0.04) than their non-obese counterparts during the luteal phase, even after adjusting for race, age, parity and education (as a marker of socio-economic status, p = 0.08). In preliminary analysis, obese women had significantly lower median estrone (E1) and progesterone (P4) plasma levels than non-obese women during the luteal phase. No significant differences were seen in the follicular phase. Conclusion: The effect of obesity on the endocrine system could alter the cervico-vaginal milieu and, thus, women's susceptibility to sexually transmitted infections. Further research is warranted to explore this causal pathway.